Molecular and clinicopathological characteristics of ERBB2 gene fusions in 32,131 Chinese patients with solid tumors - Guan, Yin; Wang, Yutong; Li, Hongxia; Meng, Jing; You, Xia; Zhu, Xiaofeng; Zhang, Qin; Sun, Tingting; Qi, Chuang; An, Guangyu; Fan, Ying; Xu, Binghe (Frontiers in Oncology, 2022)
ERBB2 amplification is one of the most important and mature targets for HER2-targeted drug therapy. Somatic mutations of ERBB2 in the tyrosine kinase domain have been studied extensively, and play a role in response to anti-HER2 therapy among different cancer types. However, ERBB2 fusion has not been got attention and its relevance to HER2-targeted therapy is unclear. We comprehensively characterized ERBB2 fusions from next-generation sequencing (NGS) data between May 2018 and October 2021 in 32,131 various solid tumors. Among the tumors, 0.28% harbored ERBB2 fusions, which occurred more commonly in gastroesophageal junction cancer (3.12%; 3/96), breast cancer (1.89%; 8/422), urothelial carcinoma (1.72%; 1/58), and gastric cancer (1.60%; 23/1,437). Our population presented with a median age of 65 years (range 28 to 88 years), a high proportion of men (55 men vs 34 women; 61.80%). Among the patients with ERBB2 fusions, TP53 (82%), APC (18%), and CDK4 (15%) were the top3 co-mutant genes. What’s more, most patients with ERBB2 fusion also had ERBB2 amplification (75.28%; 67/89), which was similar to the data in the TCGA database (88.00%; 44/50). Furthermore, TCGA database shows that patients with ERBB2 fusions in pan-cancer had a worse prognosis than those without ERBB2 fusions, as well as in breast cancer. Besides, ERBB2 amplification combined with ERBB2 fusion had a worse prognosis than those with only ERBB2 amplification. ERBB2 fusion may interfere with the effect of anti-HER2-targeted antibody drugs and influence the prognosis of patients with ERBB2 amplification. Prospective clinical trials are warranted to confirm the results in the future.